칼만 필터를 이용한 이자율 기간구조 및 부도위험 추정 - 강장구; Jang Koo Kang; 김성환; Sung Hwan Kim; 한철우; Chul Woo Han (Seonmul yeongu (Online), 2005)
논문은 한국 채권시장 내 투자등급 회사채의 수익률을 Duffie(1999)의 부도위험 모형을 이용하여 추정한다. 논문의 전반부에서는 무위험 이자율의 기간구조를 2요인 square-root 확산모형을 이용하여 추정한다. 2요인 모형의 파라미터는 한국 채권 시장의 데이터를 이용하여 준취우도추정법으로 추정한다. 관측되지않는 요인들의 값을 추정하는데는 칼만필터가 사용된다. 2요인 모형은 기간구조의 기울기와 수준에서의 random variation을 잘 표현하는 것으로 나타난다. 무위험 이자율의 기간구조를 추정한 후, 논문의 후반부에서는 모형을 회사채로 확장한다. 이때, 부도 확률이 무위험 이자율과 상관관계를 가지면서 translated square-root 확산모형을 따른다고 가정한다. 프로세스의 파라미터들은 투자등급 회사채(AAA, AA, A, BBB)를 이용하여 추정한다. 실증분석 결과는 부도위험이 무위험 이자율과 음의 상관관계를 가지며 부도위험이 낮은 등급일수록 부도위험이 더 크다는 것을 보여준다. 또한 추정된 모델은 회사채의 신용 스프레드를 성공적으로 표현하며 낮은 등급의 신용스프레드가 높은 등급에 비해 기울기가 더 급하다는 것을 보여준다. 이러한 결과들은 Duffiee의 모형이 한국 채권시장에서 관측되는 회사채 가격을 적절히 설명해준다는 것을 보여준다. This article uses a Kalman filter to fit yields of investment-grade corporate bonds to the model of instantaneous default risk, based on Duffee (1999, Review of Financial Studies, 12, pp. 197-226). The first part of this article fits the term structure of default-free interest rates to a translated two-factor square-root diffusion model. The parameters in the two-factor model are estimated by using a quasi-maximum-likelihood estimator in a state-space model in the Korean treasury bond market. A Kalman filter is used to estimate the unobservable factors. The two-factor model successfully incorporates random variations in the slope of the term structure and the level of interest rates. After estimating the default-free term structure of interest rates, the second part of this article extends the model to noncallable corporate bonds. This is done by assuming that the probability of default follows a translated square-root diffusion process with the possibility of being correlated with default-free interest rates. The parameters of the process are estimated for investment-grade corporate bonds including AAA, AA, A, and BBB. Empirical results show that the default risk is negatively correlated with default-free interest rates and confirm that the default risk is greater for lower grades. In addition, the estimated model successfully produces the term structures of credit spreads for corporate bonds and show that the credit spreads for lower grade bonds are more steeply sloped than those for higher grade bonds. These results show that Duffee’s model can reasonably account for the observed corporate bond prices in the Korean bond market. KCI Citation Count: 4